Al-bound hole polarons in TiO2 - Stashans, A. (2009)
Changes in the structural and electronic properties of TiO2 (anatase and rutile) due to the Al-doping are studied using a quantum-chemical approach based on the Hartree-Fock theory. The formation of hole polarons trapped at oxygen sites near the Al impurity has been discovered and their spatial configuration are discussed. The occurrence of well-localized one-center hole polarons in rutile may influence its photocatalytic activity. Optical absorption energy for this hole center is obtained, 0.4 eV, using the ?SCF approach. © 2009 Elsevier B.V. All rights reserved.